Stimulating inclusive outdoor play: breaking the vicious circle between physical segregation and lack of social acceptance - Visser, Kirsten; Beekhuizen, Ryan; Bloemen, Manon; Gorter, J.W.; Van Ramshorst, Karlijn; Verhoeven, Fenne; de Vries, Rosa; Wigmans, Sanne; Bolster, Eline (Routledge, 2026)
Inclusive play is a critical catalyst for social inclusion and has developmental benefits for all children. This research explores barriers that adult stakeholders perceive towards inclusion of children with disabilities in ‘playing together’ with peers with and without disabilities. Insights were gathered through four focus groups (n = 37) involving young adults with a disability, parents of children with and without disabilities, healthcare and welfare professionals, and government organizations. Key barriers identified include the segregation of daily activities of children with and without disabilities, and a lack of social acceptance, both limiting opportunities for inclusive play. Participants proposed a number of solutions, mainly focused on connecting children with and without disabilities, promoting positive attitudes, and optimizing collaboration between different stakeholders. Building local networks of healthcare and welfare professionals, municipal actors, parents, and children is crucial to creating inclusive play opportunities that benefit all children.
Keywords: Children with disabilities; adult stakeholders; inclusive outdoor play; segregation; social acceptance; Health(social science); General Health Professions; General Social Sciences